2021
DOI: 10.3389/fphys.2021.598723
|View full text |Cite
|
Sign up to set email alerts
|

Untypical Metabolic Adaptations in Spontaneously Hypertensive Rats to Free Running Wheel Activity Includes Uncoupling Protein-3 (UCP-3) and Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Expression

Abstract: Obesity and hypertension are common risk factors for cardiovascular disease whereas an active lifestyle is considered as protective. However, the interaction between high physical activity and hypertension is less clear. Therefore, this study investigates the impact of high physical activity on the muscular and hepatic expression of glucose transporters (Glut), uncoupling proteins (UCPs), and proprotein convertase subtilisin/kexin type 9 (PCSK9) in spontaneously hypertensive rats (SHRs). Twenty-four female rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Another group of rats had free excess to running wheels for 4 weeks with cessation for another 4 weeks and again access to running wheels (intermittent exercise; SHR-IR). Running distance, running time, kidney function, blood pressure, and adaptation to exercise in kidney and skeletal muscle were reported earlier for these the rats [10][11][12][13]. Briefly, running distance was 74 ± 33 km/week (Wistar) and 94 ± 16 km/week (SHR).…”
Section: Animal Modelmentioning
confidence: 76%
See 2 more Smart Citations
“…Another group of rats had free excess to running wheels for 4 weeks with cessation for another 4 weeks and again access to running wheels (intermittent exercise; SHR-IR). Running distance, running time, kidney function, blood pressure, and adaptation to exercise in kidney and skeletal muscle were reported earlier for these the rats [10][11][12][13]. Briefly, running distance was 74 ± 33 km/week (Wistar) and 94 ± 16 km/week (SHR).…”
Section: Animal Modelmentioning
confidence: 76%
“…That was, however, not the case. It might be that 4 weeks of running performance interrupted by 4 weeks of resting periods was too long to indicate such an effect as we have previously shown that an increased expression of IL-6 in skeletal muscles, an indicator of increased myokine release, was significant after 2 days but not in the IR group [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples from left ventricular tissue were used to quantify the expression of genes related to 5-HT metabolism or signaling. These samples were obtained from rats previously used for other studies as well [ 30 , 31 , 32 ]. For details of animal characteristics and blood pressure, please see [ 27 , 31 ].…”
Section: Methodsmentioning
confidence: 99%